Radar reflectivity data assimilation method based on background‐dependent hydrometeor retrieval: Comparison with direct assimilation for real cases. (3rd June 2021) - Chen, Haiqin; Gao, Jidong; Wang, Yunheng; Chen, Yaodeng; Sun, Tao; Carlin, Jacob; Zheng, Yu
Abstract: Assimilating radar reflectivity into NWP models is one of the keys to improve the accuracy of convective‐scale numerical weather prediction (NWP). There are generally two major branches of research in radar reflectivity assimilation: directly assimilating radar reflectivity, and indirectly assimilating reflectivity, i.e. assimilating hydrometeors retrieved from radar reflectivity. In this study, the indirect assimilation method based on background‐dependent hydrometeor retrievals is compared with the direct assimilation method using frequent data assimilation cycles for five real data cases. The retrieved hydrometeors in the indirect assimilation method are first verified against the hydrometeor types obtained from a polarimetric hydrometeor classification method. It is illustrated that the background‐dependent hydrometeor retrieval method can obtain reasonable model‐equivalent hydrometeors from radar reflectivity. The analysis increments for hydrometeors with both radar data assimilation methods show similar patterns but their magnitudes are different. Both quantitative and qualitative evaluations of forecasted composite reflectivities and accumulated precipitation indicate that the indirect assimilation method predicts the location and intensity of the simulated convection more accurately than the direct method. Furthermore, the indirect assimilation method is more efficient, which is valuable in real‐time applications by helping deliver forecasts quickly and thus helping forecasters make more timely warning decisions. Abstract : Comparison between the dominant hydrometeor types from a (a, c) Hydrometeor Classification Algorithm using dual‐polarization radar observations, and (b, d) the hydrometeor retrieval process in the indirect reflectivity assimilation method, valid at 2100 UTC for Case 1. (a, b) Valid at model level 20 (around 7 km AGL), while (c, d) are vertical cross‐sections along the black dashed lines in (a, b) respectively. Key Findings: The background‐dependent hydrometeor retrieval method can obtain reasonable model‐equivalent hydrometeors from radar reflectivity, verified against the polarimetric hydrometeor classification method. Quantitative and qualitative evaluations of forecasted composite reflectivities and accumulated precipitation indicate that the indirect assimilation method predicts the location and intensity of the simulated convection more accurately than the direct method. The indirect assimilation method is more efficient, which is valuable in real‐time applications by helping deliver forecasts quickly and thus helping forecasters make more timely warning decisions.